Influence of magnetic field processing on physico-chemical properties of hydrocarbon fuels - Курок, Л.М.; Матвєєва, О.Л. (Proceedings of National Aviation University (archive), 2009)
The results of researches are analyses in relation to influence of different configurations of the magnetic field on hydrocarbon fuels. It is found out, that under action of the magnetic field take place intermolecular and radical reorientation as a result of which rises oxidability power of fuel, which can be instrumental in the increase of plenitude of combustion.